PEDAGOGICAL CONDITIONS FOR DEVELOPING INFORMATION AND COMMUNICATIVE COMPETENCE OF FUTURE ENGINEERS IN THE PROCESS OF INDEPENDENT EDUCATION (American Journal of Interdisciplinary Research and Development, 2026)
This in the article independent education in the process future engineers informational and communicative competence development pedagogical conditions scientific in terms of analysis Modern education in the system information technologies intense development engineering in education new approaches demand is doing. This point of view from the point of view independent education process effective organization to grow students’ information with work, it analysis to do and professional in activity application skills to develop service does. In the study informational and communicative competence structural components, independent of education content and this competence to develop service doer pedagogical conditions illuminated. Also, digital education environment, innovative pedagogical technologies and electronic education from resources of use efficiency based on given.